Interleukin-6 Receptor Blockade can Increase the Risk of Nonalcoholic Fatty Liver Disease: Indications From Mendelian Randomization - Li, Shuxuan; Chen, Lanlan; Lv, Guoyue (Frontiers in Pharmacology, 2022)
Background: Interleukin-6 receptor (IL-6R) blockade has been approved for inflammation-associated diseases and whether it is effective in treating non-alcoholic fatty liver disease (NAFLD) is still unknown. Methods: A target-based Mendelian randomization was performed to appraise whether inhibiting IL-6 signaling pathway via IL-6R blockade can reduce the risk of NAFLD. The previous established genetic proxy SNP rs2228145 was mainly used to appraise the therapeutic effects and genetic-predicted circulating IL-6 level was treated as the exposure with ~30,000 samples. The genetic association between SNP rs2228145 (A>C) and NAFLD was obtained from non-FinnGen GWAS (1,483 cases and 17,781controls) and FinnGen GWAS (894 cases and 217,898 controls). The causal effects were estimated using a Wald ratio method and were combined using a fixed-effects meta-analysis. Furthermore, the SNP rs12048091 was employed as another proxy in the sensitivity analysis. Results: The positive control analysis suggested the SNP rs2228145 can mimic the effects of IL-6R blockade where inhibiting IL-6 signaling can reduce the risk of rheumatoid arthritis (OR = 0.68[0.58, 0.80]) and coronary heart disease (OR = 0.75[0.68, 0.84]). This Mendelian randomization analysis suggested IL-6R blockade can adversely increase the risk of NAFLD in the non-FinnGen GWAS (OR = 1.99[1.27, 3.13]) while not significant in the FinnGen consortium. The fixed-effects meta-analysis indicated inhibiting IL-6 signaling pathway can reduce the risk of NAFLD (OR = 1.80 [1.26, 2.57]). When including SNP rs12048091 as the genetic instrument, the meta-analysis using two genetic variants also indicated a similar effect on NAFLD (OR = 1.83[1.32, 2.53]). There was no heterogeneity in the whole analyses. Conclusion: Our Mendelian randomization suggested inhibiting IL-6 signaling pathway via IL-6R blockade might increase the risk of NAFLD, suggesting IL-6R should play a protective role in NAFLD.